1998
DOI: 10.1029/98jb01391
|View full text |Cite
|
Sign up to set email alerts
|

The formation and evolution of layered structures in porous media

Abstract: Abstract. Horizontally layered structures can develop in porous or partially molten environments, such as magma chambers, the early Earth's mantle, and hydrothermal systems. We have studied the generation and evolution of these horizontally layered structures in a rigid porous medium by heating a compositionally stably stratified fluid from below. Growth of a convective layer through entrainment, the formation of a vertical density interface on top of this layer and destabilization of the next layer are closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Previous studies, in which the formation and evolution of convective layers in porous media were investigated under idealized £uid conditions, have shown that a force balance on a £uid parcel just beneath the interface between the two £uid layers determines the stability of layered system [17,18]. In the context of the ridge-crest system, this balance states that the stability of the brine layer is mainly determined by (1) the brine salinity established by the thermodynamical conditions, and (2) the hydrological properties of the basaltic rocks that host the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, in which the formation and evolution of convective layers in porous media were investigated under idealized £uid conditions, have shown that a force balance on a £uid parcel just beneath the interface between the two £uid layers determines the stability of layered system [17,18]. In the context of the ridge-crest system, this balance states that the stability of the brine layer is mainly determined by (1) the brine salinity established by the thermodynamical conditions, and (2) the hydrological properties of the basaltic rocks that host the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Ž . Schoofs et al, 1998 . First, transport of heat solute across the interface changes from convective entrain-Ž .…”
Section: Self-limitation Of the Conõectiõe Layersmentioning
confidence: 99%
“…to generate layered structures Schoofs et al, 1998 . In this so-called Hele-Shaw approximation, however, heat and solute advect at the same speed, which is fundamentally different from flow through a geological medium having a low porosity.…”
Section: Introductionmentioning
confidence: 99%
“…At the temperatures and pressures within the marine sediments, the gas (usually Methane) is in solution. Systematic experimental observations of flow and density profile of methane gas are severely limited due to uncontrollable parameters such as changes in pressure and temperature gradients and morphological variations of the host matrix, i.e., the evolution of porous ground [5][6][7]. One of the major problems in modeling such a complex system is to incorporate all the details on a large scale [11].…”
mentioning
confidence: 99%
“…The response of the flow rate density to the temperature is nonlinear. Understanding the flow of methane gas below the ocean floor is of considerable interest particularly in context to geochemical and geophysical characteristics of methane hydrate in marine sediments [1][2][3][4][5][6][7][8][9][10]. At the temperatures and pressures within the marine sediments, the gas (usually Methane) is in solution.…”
mentioning
confidence: 99%